Surface modification of biochar derived from gaharu waste via pyrolysis: article - Mohd Azmi, Mohd Darul Imran; Noor Ismail, Kamariah (2017)
Biochar is a solid material obtained from the carbonization of biomass. This research objective is to produce biochar derived from gaharu waste. The gaharu waste was taken from Bukit Larut, Perak. The production biochar was at 3 different temperature, 400oC, 500oC and 600oC. This research also analyzes the adsorption ability of the biochar using methylene blue. The biochar undergoes modifications using H3PO4, NaOH and hot water before the analysis was being performed. The yield of the biochar produced was 42%, 38% and 24% for 400 oC, 500 oC and 600oC respectively. The adsorption of methylene blue for H3PO4 modification was 0.3547mg/g , 0.2678mg/g and 0.2590mg/g for 400 oC, 500 oC and 600oC respectively. For NaOH modification, the adsorption value was 0.8706mg/g for 400 oC, 0.7305mg/g for 500 oC and 0.8076mg/g for 600 oC. The adsorption of methylene blue for hot water modification was 0.8830mg/g, 0.7083mg/g and 0.7681mg/g for 400 oC, 500 oC and 600oC respectively. The optimum temperature to produce biochar was 400oC and the chemical modifications using NaOH and hot water can increase the ability of methylene blue adsorption.